Trends in Insect Molecular Biology and Biotechnology (Springer International Publishing, 2018)
This book provides an overview on the basics in insect molecular biology and presents the most recent developments in several fields such as insect genomics and proteomics, insect pathology and applications of insect derived compounds in modern research. The book aims to provide a common platform for the molecular entomologist to stimulate further research in insect molecular biology and biotechnology. Insects are one of the most versatile groups of the animal kingdom. Due to their large population sizes and adaptability since long they attract researchers' interest as efficient resource for agricultural and biotechnological purposes. Several economically important insects such as Silkworms, Honey Bee, Lac and Drosophila or Termites were established as invertebrate model organisms. Starting with the era of genetic engineering, a broad range of molecular and genetic tools have been developed to study the molecular biology of these insects in detail and thus opened up a new horizon for multidisciplinary research. Nowadays, insect derived products are widely used in biomedical and biotechnology industries. The book targets researchers from both academia and industry, professors and graduate students working in molecular biology, biotechnology and entomology.